Managing big data integration in the public sector - Aggarwal, Anil (Advances in public policy and administration (APPA) book series., 2016)
This book is a pivotal reference source of scholarly research on the application of big data analytics in government contexts and identifies various strategies in which big data platforms can generate improvements within that sector.